2023
DOI: 10.3847/1538-4357/acb334
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Loop Quantum Gravity from the Event Horizon Telescope Results of Sgr A*

Abstract: The Event Horizon Telescope (EHT) collaboration’s image of the compact object at the Galactic center is the first direct evidence of the supermassive black hole (BH) Sgr A*. The shadow of Sgr A* has an angular diameter d sh = 48.7 ± 7 μas with fractional deviation from the Schwarzschild BH shadow diameter δ = − … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 128 publications
(164 reference statements)
0
16
0
Order By: Relevance
“…By comparing with EHT observations [67][68][69][70][71][72], we can constrain the value of polymeric function P in LQG. Although analytical calculations [36,87] can determine the shadow silhouette cast, in reality, the accretion disk produces extended emission around the photon ring, which significantly alters the shadow morphology. The impact of plasma and metric on the BH images was investigated earlier [88,89], which shows the size of the luminous ring is greatly influenced by both of them.…”
Section: Semi-analytical Simulation Of Shadow Images Of Lqbhmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing with EHT observations [67][68][69][70][71][72], we can constrain the value of polymeric function P in LQG. Although analytical calculations [36,87] can determine the shadow silhouette cast, in reality, the accretion disk produces extended emission around the photon ring, which significantly alters the shadow morphology. The impact of plasma and metric on the BH images was investigated earlier [88,89], which shows the size of the luminous ring is greatly influenced by both of them.…”
Section: Semi-analytical Simulation Of Shadow Images Of Lqbhmentioning
confidence: 99%
“…Considering that dimensionless spin a is also proportional to the gravitational constant, which also needs to be scaled by a factor of (1 + P ) 2 /(1 − P ) 2 . We should note that [87] uses the gravitational constant G LQG rather than the Newtonian gravitational constant G N in their comparison between the shadow image data and LQBH with different polymeric functions. Therefore, the result of our work is expected to be different from [87].…”
Section: A Brief Introduction To Lqbh Spacetimementioning
confidence: 99%
See 1 more Smart Citation
“…The boundary of the shadow is determined by the photon ring, which principally relies on the black hole's parameters [68]. The application of the shadow in understanding near-horizon geometry has sparked a flurry of activity in analyzing, both analytically and numerically, shadows for black holes in GR [12,34, and in LQG [53,54,[91][92][93]. The EHT observation unveiled the shadows of supermassive black holes Sgr A* and M87* [1,94] whose sizes are within 10 percent of the Kerr predictions, furnishing another tool to explore the nature of strong-field gravity.…”
Section: Constraints From Eht Observations Shadows Of M87* and Sgrmentioning
confidence: 99%
“…Theoretical studies of BH shadows for different gravity models and BH solutions can be found in . After the first ever observation of the BH shadows of M87 and Sgr A * in 2019 [19] and in 2022 [21], the observations have been developed by various authors [91][92][93][94][95][96][97][98].…”
Section: Introductionmentioning
confidence: 99%